A Double-Edged Sword: The Modernist Dutch Reformed Church of Op-die-Berg. Issue 3 (2nd September 2019) - Tymbios, Marijke Andrea
ABSTRACT: Although not monuments in the traditional sense, modernist Afrikaans Protestant churches erected during the 20th century are reminders of the wealth of the Afrikaner people, the stringent union of Church and State, and the Afrikaner nation's ambition to align themselves with the developed Western world during apartheid. The number of churches built in multiple South African cities and towns attests to the Afrikaners' need to establish a modern and future-oriented visual identity. The rationale behind adopting modernism for these churches is complex and multi-layered. It allowed Afrikaner architects, such as A. P. S. Conradie, to experiment with church design and mould structures according to their personal preferences. Conradie's designs encompassed Frank Lloyd Wright's notion of "organic architecture", whilst blending vernacular architecture and his personal religious beliefs to create, arguably, some of the finest examples of modernist church architecture in South Africa. Due to the socio- political climate at the time of construction, these churches are associated with the period of Afrikaner nationalism. Yet, measured against their contribution to the development of local architecture, they constitute important remnants of modernism in the built environment. This article briefly investigates this phenomenon in reference to Conradie's church for the Op-die- Berg Dutch Reformed congregation.